Well-Being as Human Development, Equality, Happiness and the Role of Freedom, Activism, Decentralization, Volunteerism and Voter Participation: A Global Country-Level Study - Perkins, Douglas D.; Ozgurer, Mehmet Reha; Lupton, Andrew; Omidvar-Tehrani, Shadi (Frontiers in Psychology, 2021)
We propose and test a new model for predicting multiple quantitative measures of well-being globally at the country level based on the United Nations Human Development Index (HDI), income inequality (Net Gini), and National Happiness Index (NHI; U.N. Sustainable Development Solutions Network world survey of life satisfaction). HDI consists of per-capita Gross National Income (economic well-being), average life expectancy (proxy for health well-being), and educational attainment (capabilities well-being). Using data on 105 countries representing 95% of the world’s population, a history of grassroots activism (Global Non-violent Action Database), civil liberties and political rights (Freedom Score), political and fiscal decentralization, and voter participation (Institute for Democracy and Electoral Assistance) correlate with HDI and NHI. Citizen volunteering (Gallup Civic Engagement Index) predicts only NHI. In multivariate analyses, Freedom Score is the most robust predictor of all well-being measures, including income equality. Fiscal decentralization and voter turnout also predict HDI and NHI, controlling for other influences. Based on prior analyses in the Global Development of Applied Community Studies project, implications and recommendations are discussed for developing community human research and professional resources across 12 disciplines in countries where they are needed based on social justice, citizenship, well-being, inequality, human rights, and other development challenges. We recommend individual and community-level and qualitative analyses of the above predictors’ relationships with these same conceptualizations of well-being, as well as consideration of other social, cultural and political variables and their effect on well-being.